The Principal's Leadership Role in Improving School Administrative Effectiveness: A Qualitative Study at SDN 23 Talang Kelapa - Bety Kurniasari; Alhadi Yan Putra; Mahasir (Graduate Program Magister Manajemen Pendidikan, 2026)
This study aims to describe the role of the principal in improving the effectiveness of administrative administration at SDN 23 Talang Kelapa. The focus of the study includes the principal's role in planning, implementing, organizing, supervising, and evaluating administrative administration programs, as well as identifying obstacles and solutions in the implementation of school administration. This study uses a descriptive qualitative approach implemented at SDN 23 Talang Kelapa, Banyuasin Regency. The participants consisted of one principal, two teachers, two administrative staff members, and one school committee representative selected through purposive sampling. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and conclusion drawing, while data validity is tested using source and method triangulation techniques. The results of the study indicate that the principal has an important role in improving the effectiveness of administrative administration through the preparation of work programs, division of administrative tasks, supervision of administrative services, and periodic evaluation of the implementation of school administration. Unlike previous studies that primarily focused on managerial leadership and teacher performance, this study specifically examines the principal's integrated role in planning, organizing, implementing, supervising, and evaluating school administration to improve administrative effectiveness at the elementary school level. This research is beneficial in the fields of educational management, school administration, and educational leadership, particularly as a reference for principals, administrative staff, and elementary education managers in improving the quality of school administrative services. The novelty of this research lies in its comprehensive study of the principal's role in improving administrative effectiveness through integrated planning, implementation, organization, supervision, and evaluation at the elementary school level.